1997
DOI: 10.1007/s004280050088
|View full text |Cite
|
Sign up to set email alerts
|

Expression of pancreatic digestive enzymes in normal and pathologic epithelial cells of the human gastrointestinal system

Abstract: Pancreatic digestive enzymes have rarely been reported in human nonpancreatic organs. We examined their expression in the epithelial cells of the nonpancreatic gastrointestinal organs, looking for pancreatic alpha-amylase, trypsin, chymotrypsin and pancreatic lipase. Western blotting, enzyme assay and pancreatic alpha-amylase mRNA were also used in selected specimens. In normal tissues, immunoreactivity of one or more of these enzymes was frequently noted in cells of the salivary glands, stomach, duodenum, lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…Kim et al (4) reported trypsin activity in 6/29 human ductal adenocarcinomas, yet active pancreatic lipase only in 1/29. Terada et al (8) reported pancreatic lipase in half of their cases but none of the two groups examined CEL expression. In line with our data other investigators (9,10) noted CEL transcription in 6 examined pancreatic tumor cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kim et al (4) reported trypsin activity in 6/29 human ductal adenocarcinomas, yet active pancreatic lipase only in 1/29. Terada et al (8) reported pancreatic lipase in half of their cases but none of the two groups examined CEL expression. In line with our data other investigators (9,10) noted CEL transcription in 6 examined pancreatic tumor cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Acinar enzymes are expressed in adenocarcinomas of the pancreas (4,7,8) and pancreatic cell lines (9,10). Therefore, pancreatic adenocarcinoma-specific CEL expression is feasible but has not been verified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the nucleotide sequence of TAT-2 and pancreatic trypsin-2 is identical (Sorsa et al, 1997). Since then, trypsinogen immunoreactivity or mRNA has been detected in various cancers like stomach, pancreas, ovary, lung, bladder, esophagus, bile duct, and colon cancers, and carcinoma cell lines (Bernard-Perrone et al, 1998, Hirahara et al, 1995, Hotakainen et al, 2006, Koivunen et al, 1991b, Koshikawa et al, 1992, Koshikawa et al, 1994, Miyagi et al, 1995, Miyata et al, 1999, Nyberg et al, 2002, Ohta et al, 1998, Oyama et al, 2000, Paju et al, 2004, Terada et al, 1995, Terada et al, 1997, Yamashita et al, 2003.…”
Section: Extrapancreatic Trypsinogen Expressionmentioning
confidence: 99%
“…Subsequent in vivo and in vitro immunohistochemical and morphological studies have described several types of intermediate cells in normal and pathological human pancreas [Ulich et al, 1982;Ohta et al, 1994;Terada et al, 1997;Aughsteen, 1999], in streptozotocin-diabetic transgenic mouse pancreas [Gu et al, 1997], in streptozotocindiabetic hamster pancreas subjected to in vitro incubation with local pancreatic growth factors [Rosenberg et al, 1996], and in rat and human pancreases subjected either to subtotal surgical pancreatectomy or to partial duct ligation [Rosenberg, 1995;Bertelli and Bendayan, 1997;Szynaka et al, 1997]. These cells have been classified into acinar-ß (acinar cells containing ß-granules), acinar-· (acinar cells containing ·-granules), ß-acinar (ß-cells containing acinar zymogen granules), ·-acinar (·-cells containing acinar zymogen granules), and duct acinar (excretory duct cells containing amylase) cells.…”
Section: Introductionmentioning
confidence: 99%